Meeting the unique needs of gifted and talented learners in Nigerian schools: support options (2017)
It has always been the assumption of the generality of the people that gifted and talented children have been so much intellectually endowed by the Almighty God that they do not need the support of anybody in order to succeed in whatever they do. However, the most acceptable definition of gifted children describe them as those who require differentiated educational programmes and services beyond those normally provided by the regular programme. The implication of this is that gifted children have special educational, social and emotional needs that differ from those of other children. To meet those needs a special type of "good" teacher is required. The role the parents could also play in order to meet the unique needs of these children cannot be overemphasized. It is against this background that this study examined the essential characteristics of effective teachers of gifted students, the qualities expected of such teachers and the strategies to be adopted in supporting the gifted learners in the school. Classroom management support that can be given to gifted learners was also examined. Finally, it was recommended for teachers to always create a learning environment that is open, accepting, warm, and intellectually challenging, and to always value the achievement of high ability students. Recommendation was also made for the parents to establish a close, mutually respectful relationship with their children and to provide very often an intellectually stimulating curiosity producing atmosphere in their homes.